TINJAUAN YURIDIS PELAKSANAAN KONTRAK BISNIS PADA PT PERTAMINA (PERSERO) DENGAN ANAK PERUSAHAAN - , Vidya Angeliasari, SH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In this era of globalization, Indonesia, as developing countries are now actively rebuilding their country in all areas where one of them in the oil and gas industry which provided the largest deficit of PT Pertamina (Persero) as an State Owned Oil Company. With the establishment of subsidiaries for business development related to the diversification efforts undertaken in order to provide added value and support the main business of PT Pertamina (Persero). The establishment of Subsidiary for the development of related businesses is related to the diversification efforts undertaken in order to provide added value and support the main business of PT Pertamina (Persero. In every transaction between PT Pertamina (Persero) with subsidiaries in accordance with the principles of mutually beneficial business rules. In realization of business contractual arrangements between PT Pertamina (Persero) with subsidiaries, and roles and responsibilities of Directors in carrying out and completion of the contract is done, as we know it is not described in detail in laws and regulations in Indonesia. This research was conducted using this method is that the normative juridical approach that focuses on library research to obtain secondary data and materials are grouped in accordance to the laws of certain criteria. The method of research used secondary data research material consists of primary legal materials, legal materials and field research is secondary data searches conducted through interviews with relevant parties. Thus the results of analysis concludes by using deductive logic. Based on the research note that it is not a regulation on the responsibilities of directors of parent companies and subsidiaries execution and settlement of contractual issues. Act related only to explain the duties and obligations of the Board of Directors of the Company in general, so that PT Pertamina (Persero) in settlement of legal issues following the ideal form of business contracts in Indonesia, which according to rules and regulations in Indonesia which adheres to the principle of freedom of contract. The Directors shall perform duties in good faith and full responsibility for the interest and business of the Company in accordance with applicable regulations.